Implementation of a radar prototype on an unmanned arial vehicle - Liu, Jianrong (2014)
This project aims to implement a Synthetic Aperture Radar (SAR) prototype using Frequency Modulated Continuous Wave (FMCW) on an Unmanned Arial Vehicle (UAV). Coupled with the PC-104 as the control of the whole system, that has the stacking capability to add on stackable modules, namely, Field-Programmable Gate Array (FPGA), A/D, power supply and wireless telemetry module that are needed for this project. As the second batch of the project, a group of three FYP students will be looking into, UAV, Data analysis and last but not handling the real-time programming that involves SAR data processing using FPGA so as to achieve longer flight time before the on board storage is full. In this report, the different stages of data processing, the types of SAR image formation algorithm and lastly software like Xilinx and MATLAB will also be discussed and implement.